Agonism of GPR120 Prevented High Glucose-Induced Apoptosis of Retinal Endothelial Cells through Inhibiting NLRP3 Inflammasome - Ding, Xiaoju; Xie, Haijuan; Shan, Wuqiang; Li, Ligang (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose GPR120 has been reported to ameliorate inflammation in diabetes and diabetic complications. In this study, GW9508, the GPR120 agonist, was utilized in human retinal microvascular endothelial cells (HRMECs) exposed to high glucose (HG) to investigate the involvement of GPR120 in cellular viability and apoptosis as well as the association with the NLRP3 inflammasome.Methods The expression of GPR120 in HRMECs cultured under HG was firstly detected by Western blotting. HRMECs were then assigned to the normal control, GW9508, HG, and HG + GW9508 groups. The expression of the NLRP3 inflammasome consists of NLRP3, ASC, and caspase-1 and was detected by Western blotting and the downstream IL-1β and IL-18 by ELISA. The cellular viability and apoptosis of HRMECs were detected by CCK-8 and flow cytometry, respectively. The expressions of apoptosis-related proteins Bax and Bcl-2 were detected by Western blotting. Finally, nonspecific siRNA (NS) or GPR120 siRNA (siGPR120) was transfected to the cells, followed by stimulation with or without GW9508 or HG, and the expression of NLRP3, ASC, and caspase-1 were detected by Western blotting in these groups.Results GPR120 is expressed in HRMECs, and HG can reduce its expression in a time-dependent manner. GW9508 can attenuate inflammation by reducing the expression of NLRP3, ASC, caspase-1, IL-1β, and IL-18 under HG. GW9508 rescues the viability of HRMCs and reduces cell apoptosis by preventing an increase in Bax expression and the reduction in Bcl-2 expression. Additionally, knockdown of GPR120 by siRNA weakened the effects of GW9508 on NLRP3 inflammasome expression.Conclusions Activation of GPR120 protects retinal vascular endothelial cells from HG through inhibiting NLRP3 inflammasome. Thus, GPR120 might be a potential therapeutic target to reduce retinal endothelial damage in diabetic retinopathy.
Keywords: diabetic retinopathy; GPR120; GW9508; high glucose; retina vascular endothelial cell